OTODYSTROPHY - A CASE REPORT - Pires, Joana (2006)
Osteitis is a group of disease that provoke alterations of bone metabolism and growth. Paget's disease, Osteopetrosis, Osteogenesis lmperlecta, Otosclerosis, Fibrous Dysplasia are otodystrophies that are clinically, radiologically and pathalogically distinct. The characteristics of the different otodystrophies are reviewed and the data of a patient presented with the suggestion that the reoder determines the diagnosis.